Living Hadis of Tolerance in Multicultural Education: A Leadership Study in Pesantren Al Mukmin Ngruki Sukoharjo Surakarta - bin Salman, Abdul Matin (Jurnal Pendidikan Islam, 2017)
Pesantren (Islamic Boarding School) Al-Mukmin Ngruki is underestimated by some of the Indonesian people. It is considered as the center of radical teachings that have no tolerance to others. But in fact, the values of tolerance can be found in the teaching materials. With Bayani and Burhani approaches in understanding the religious source, pesantren Al-Mukmin persists to implant the values of tolerance to the students in the learning process, such as behave positively toward differences and plurality. The leaders of pesantren make those values as the starting point to strengthen multicultural education in pesantren with role modeling, habituation, attention, and advice in living those values.